2020
DOI: 10.1002/jbmr.3955
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Hypophosphatemia: Uniquely Mild Disease Associated With PHEX 3′-UTR Mutation c.*231A>G (A Retrospective Case–Control Study)

Abstract: X-linked hypophosphatemia (XLH), the most prevalent heritable renal phosphate (Pi) wasting disorder, is caused by deactivating mutations of PHEX. Consequently, circulating phosphatonin FGF23 becomes elevated and hypophosphatemia in affected children leads to rickets with skeletal deformity and reduced linear growth while affected adults suffer from osteomalacia and forms of ectopic mineralization. In 2015, we reported uniquely mild XLH in six children and four of their mothers carrying the non-coding PHEX 3 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Earlier, small cohort studies identified c.*231A>G as a disease‐causing variant in multiple probands leading to XLH (Ichikawa et al, 2008 ; Smith et al, 2020 ), however, these studies did not detect CNV, so it is not known whether these patients also carried the Ex‐13–15 duplication. The recent readout from the hypophosphatemia genetic testing program found that all XLH patients who had the 3′‐UTR c.*231A>G variant also carried the Ex13–15 duplication, but one affected proband carried the duplication without the c.*231A>G variant, suggesting that the duplication can contribute to disease on its own (Rush et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Earlier, small cohort studies identified c.*231A>G as a disease‐causing variant in multiple probands leading to XLH (Ichikawa et al, 2008 ; Smith et al, 2020 ), however, these studies did not detect CNV, so it is not known whether these patients also carried the Ex‐13–15 duplication. The recent readout from the hypophosphatemia genetic testing program found that all XLH patients who had the 3′‐UTR c.*231A>G variant also carried the Ex13–15 duplication, but one affected proband carried the duplication without the c.*231A>G variant, suggesting that the duplication can contribute to disease on its own (Rush et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Genetic testing by Sanger sequencing or next-generation sequencing is readily available in several genetic centers in Belgium for PHEX as well as for other skeletal dysplasia genes using a whole-exome sequencing-based gene panel. Genetic testing also examines the 3' untranslated region in which mutations associated with milder XLH phenotypes have been reported (111)(112)(113). In general however, mutations can affect any exon, without a clear genotype-phenotype correlation (114).…”
Section: Genetic Testingmentioning
confidence: 99%
“…Recently, the c.*231A>G variant was reported to be associated with mild disease severity in a small cohort. ( 88 ) However, within our cohort, a wide spectrum of clinical features was reported for patients with both the gain of exons 13–15 and the c.*231A>G variant. Supporting our result, another large family with these variants, tested through the program, was recently reported to have symptoms with a wide spectrum of severity, including hearing loss.…”
Section: Discussionmentioning
confidence: 65%